The Dead Sea scrolls and contemporary culture: proceedings of the international conference held at the Israel Museum, Jerusalem (July 6-8, 2008) - Roitman, Adolfo Daniel; Schiffman, Lawrence H.; Tzoref, Shani (Studies on the texts of the desert of Judah, 2011)
Some thoughts at the close of the Discoveries in the Judaean Desert Publication Project / Emanuel Tov -- The Groningen hypothesis revisited / Florentino Garcia Martinez -- 1QS 6:2c-4a -- satellites or precursors of the Yaḥad? / Charlotte Hempel -- What kind of sect was the Yaḥad?: a comparative approach / Eyal Regev -- The pre-history of the Qumran community with a reassessment of CD 1:5-11 / James C. Vanderkam -- The Elohistic psalter and the writing of divine names at Qumran / Jonathan Ben-Dov -- Non-Masoretic variant readings in the Hebrew University Isaiah scroll (1QIsab) and the text to be translated / Peter W. Flint -- Clearer insight into the development of the Bible -- a gift of the scrolls / Eugene Ulrich -- Biblical interpretation in the Dead Sea scrolls: looking back and looking ahead / Moshe J. Bernstein -- Revelation and perspicacity in Qumran hermeneutics? / James H. Charlesworth -- The Genesis apocryphon: a chain of traditions / Esther Eshel -- From paratext to commentary / Armin Lange -- Enochic Judaism: an assessment / John J. Collins -- Between Qumran sectarian and non-sectarian texts: the case of Belial and Mastema / Devorah Dimant -- Which is older, Jubilees or the Genesis apocryphon?: an exegetical approach / James Kugel -- Pseudepigraphy and first person discourse in the Dead Sea documents: from the Aramaic texts to writings of the Yaḥad / Loren Stuckenbruck -- Ritual purity / Hannah K. Harrington -- Dogs and chickens at Qumran / Jodi Magness -- Creative interpretation and integrative interpretation in Qumran / Vered Noam -- The price of mediation: the role of priests in the priestly halakhah / Cana Werman -- From Jesus to the early Christian communities: modes of sectarianism in the light of the Dead Sea scrolls / George J. Brooke -- The Gabriel revelation / Israel Knohl -- Nascent Christianity between sectarian and broader Judaism: lessons from the Dead Sea scrolls / Serge Ruzer -- Rethinking gender in the community rule: an experiment